Progress of dexmedetomidine in preventing postoperative delirium in elderly patients - DENG Meng*，LIU Ximei，WANG Yuan，ZHENG Beibei (Zhongguo linchuang yanjiu)
Postoperative delirium occurs as a result of multifactorial effects，and as a common perioperative neurological complicationin elderly patients，the current limited treatment options are not effective in improving the prognosis, so the prevention of postoperativedelirium will be essential. As a commonly used perioperative sedative drug, dexmedetomidine (Dex) has unique sedative, analgesic, and anti⁃inflammatory effects, which may exert multifactorial prevention of postoperative delirium in elderly patients through multiplepathways. Therefore，this review aims to describe the potential value of Dex’s multi-pathway prevention of postoperative delirium inelderly patients, suggesting that Dex may become an important component of strategies for preventing postoperative delirium.